Upaya Meningkatkan Hasil Belajar Siswa Menggunakan Model Pembelajaran Projek Based Learning - Evandel, Kervan; Indrawan, Eko; Primawati, Primawati; Wulansari, Rizky Ema (YASIN, 2024)
This research evaluates the application' of the Project' Based Learning' (PjBL)' learning model in Creative Products and Entrepreneurship subjects in class' XI Heavy' Equipment Engineering' at SMK Negeri 1 Timpeh. SMK Negeri 1 Timpeh strives to achieve the vision of the Revitalization of SMK PK, which emphasizes the preparation of graduates for the world of work or entrepreneurship. Interview results show' that student' learning outcomes' have not reached' graduation standards, and teacher-centred learning conditions and a lack of variety in learning models are the main challenges. Therefore, this research applies the PjBL model as an effort to overcome this problem. The PjBL model is considered the right solution because it emphasizes time-bound processes, focus on problems, and the formation of meaningful learning units. This research includes the results of previous research that shows the success of PjBL in improving student learning outcomes in various educational contexts. This research used method Classroom Action Research (PTK) with an instrument in the form of a project assessment rubric. The research results show a big improve in student learning outcomes after implementing PjBL. In the second cycle, classical completion reached 100%, exceeding the research success indicator. The PjBL model provides alternative options for teachers in learning approaches, creates fun learning experiences, and increases student engagement. It is hoped that the implementation of PjBL can activate students, increase creativity, and produce graduates with skills relevant' to' the demands' of the 21st' century.' This research supports the implementation of PjBL to improve student' learning' outcomes' in Creative Products' and Entrepreneurship' subjects.